Peranan Pengembangan Karier Dalam Meningkatkan Kinerja Karyawan Di PT PLN Nusantara Power Service - Nadyah Amelia Putri; Ni Made Ida Pratiwi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research found that there is a positive relationship between career development and employee performance. Career development, both individual and organizational, has a positive impact on employee motivation, loyalty and productivity. This journal also highlights the importance of career planning for both individuals and organizations, and discusses the stages of career development and the factors that influence them. This journal concludes that career development is an important aspect in human resource management. By paying attention to the factors discussed, individuals and organizations can work together to achieve better career development goals.